Castor-Based Ester Oil Production Using SnCl₂/HZSM-5 Catalyst for Sustainable Transformer - Istiqomah; Widayat Widayat; John Philia; Sriyono; Kevin Gausultan Hadith Mangunkusumo; Aji Suryo Alam; Hadiyanto (Emerging Science Journal, 2026)
Mineral oil remains the most common insulating fluid in power transformers; nevertheless, its non-biodegradable nature and carbon-based emissions have prompted the quest for environmentally safer alternatives. Castor oil, a sustainable and non-edible derivative, provides a promising source for high-performance ester-based insulating lubricants. This study investigates the synthesis and process optimization of castor-based polyol esters via esterification with trimethylolpropane using a heterogeneous SnCl₂/HZSM-5 catalyst. The alcohol-to-oil molar ratio, temperature, and catalyst loading were among the critical reaction parameters that were modeled and optimized using response surface methods with a central composite design. Under optimized conditions of 130°C and 2.207 wt% catalyst, an ester yield of 81.77% was obtained. The resulting ester oil demonstrated advantageous characteristics, such as acceptable color and dielectric performance, while viscosity and acidity were improved by a two-step process to comply with the IEC 62975:2021 standards for distribution transformer insulating oils. The statistical study validated the model's reliability, with ANOVA indicating a substantial quadratic regression (R² = 0.952). The key novelty of this work lies in demonstrating the potential of SnCl₂/HZSM-5 to catalyze the synthesis of castor-derived polyol esters with tailored physicochemical properties, supporting their future scalability and use as sustainable insulating oils.